Inovasi Bumdes dalam Memenuhi Kebutuhan Air Bersih di Desa Laren - Sundari, Ariefah; Ainiyah, Latifatul; Haniyah, Nailul Aisyiyal; Sari, Melani Putri Dewita (Penerbit Goodwood, 2024)
Purpose: To address the issue of high lime content in groundwater in Laren Village, making it unsuitable for consumption, BUMDes Jaya Abadi implemented several innovations to improve clean water access. Research Methodology: This qualitative case study uses a phenomenological approach, exploring innovations through in-depth interviews, observations, and document analysis. Key informants included BUMDes managers, local residents, and government officials. Results: The innovations increased clean water production from 10 m³ to 30 m³ per day and raised village revenue by 20 million rupiah annually. The adoption of solar-powered pumps and nanotechnology-based filtration reduced environmental impact by minimizing reliance on fossil fuels and harmful chemicals. Conclusions: The study highlights the importance of technological and managerial innovations in rural water management and provides a replicable model for other villages. Limitations: The study is limited by its focus on a single village and the short timeframe for assessing long-term impacts. Contribution: This study contributes to the broader discourse on sustainable rural development and the role of local enterprises in addressing water scarcity.